An Automatic System for Non-Uniform Brightness Compensation of LED Arrays: Image Processing Routines to Locate LED Centers - KURDTHONGMEE, Wattanapong; LAMSUB, Taofik (Walailak Journal of Science and Technology (WJST), 2011)
To be able to accurately study the effect of light on the growth of plants or some living organisms, a light source must be capable of changing its wavelength, brightness and exposure duration. Light Emitting Diodes (LEDs) have many benefits for use in this application. To be applicable, the light source needs to be integrated into a panel consisting of thousands of variable wavelength LEDs. Inside the panel, LEDs normally yield significant variations in brightness of around 15 to 20 % or more unless there is a fine selection of matched LEDs. In this paper, the problems and previously proposed solutions to the variations in brightness of LEDs are addressed and proposed automatic image processing based routines are presented. The routines have been proved to correctly locate the positions of almost all LEDs in the panel.